(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, the author outlined why it is important to include people with disabilities in the life of society. There are tens of millions of people living in the world with various characteristics of physical and mental development. Like everyone else, they should be able to fully participate in society. Let’s understand what inclusivity is and how it can change the entire society for the better.